A world of empires United States rule in the Philippines, 1898-1913 - Morrison, Christopher Allen (ProQuest LLC, 2009)
This dissertation examines important policymaking episodes in the first fifteen years of U.S.-Philippine colonial history. These include the formation of an American colonial government, a currency reform campaign, the creation of an opium control regime, the establishment of an agricultural bank, and the response to Japanese imperialism. In each case, interaction with other empires significantly shaped United States colonial rule in the Philippines. Americans' studying and borrowing of ideas from other colonial powers were part of a pragmatic approach to colonial policy making. Although American policy models and ideas played a role, the American-Philippine colonial project was not an ideological attempt to remake the Philippines in the image of the United States. U.S. rule in the Philippines had more limited goals aimed at stability and some economic development, and Americans sometimes adopted other powers' ideas to achieve these goals. This interaction with other empires was part of a U.S. approach to foreign relations during the period that emphasized international cooperation. This study also shows the impact that engagement with other empires had on American exceptionalist attitudes about colonialism--Abstract.